EVALUATING THE INFLUENCE OF THE MOTHER TONGUE (L1) ON THE ACQUISITION OF ENGLISH LANGUAGE (L2): A CASE STUDY OF ASSEMBLIES OF GOD SENIOR HIGH SCHOOL IN THE KWADASO SUB - METRO OF GHANA. - Adade-Yeboah, Asuamah; Okoh Agyemang, Festus; Appiah, George; Poku, Samuel Osei (Advances in Social Sciences Research Journal, 2017)
Studies in contact linguistics have shown that when two languages come in contact, they interfere with each other grammatically and lexically, producing different contact phenomenon. This study sought to test how English and Twi languages manifest such a phenomenon. This was done by looking at how they experience cohesion as well as how they influence each other when they come into contact using the contact phenomenon theories of cohesion and bilingualism as found in Halliday and Hasan’s (1976). In all, 84 students who were reading Ghanaian Language (Twi) as one of their major subjects were purposively selected using the Assemblies of God Senior High School, Kumasi, Ghana, as a case study. The study’s analysis was purely qualitative and indicated that both languages; Twi (L1) and English(L2) realize cohesion by means of reference, substitution, ellipsis, conjunction and by lexical cohesion as observed by Halliday and Hasan (1976). However, the study saw differences in the languages’ use of reference and ellipsis. Also, both Twi and English were identified to have influence on each other when they come into contact. Among other recommendations, the study recommended that teachers should come up with teaching methods that are interactive in the English curriculum so as to ensure that students are given an opportunity to interact with each other in English. Also, teachers and translators of Twi and English should be conscious of the differences and similarities in the way the language works to enable them handle teaching and translation with ease and professionalism.